The Impact of the EU Blue Card Policy on Economic Growth in the African Sending Countries - d'Artis Kancs; Pavel Ciaian (Economics and Econometrics Research Institute (EERI), 2010)
In 2009 the EU adopted a new migration policy instrument - the Blue Cards (BC) - for attracting highly skilled workers to the EU. The present paper examines the potential impacts, which BC may cause on the less developed sending countries (LDC). According to the adopted framework of innovative capital, the BC will reduce human capital in LDC. In addition, BC will also have a negative impact on knowledge capital. These findings suggest that the BC is not coherent with the EU's development policy. Without appropriate policy responses, BC fade the developing country growth prospects away. In order to address the skill drain issues, we propose and examine alternative migration policy options for the LDC.
Keywords: F02; F22; J24; J61; O15; 330; African sending countries; high-skill migration; EU Blue Cards; innovative capital; economic growth; LDC